QUALITATIVE STUDY ON LANGUAGE SKILL ASSESSMENT WITH QUIZIZZ AT SMA TUNAS BANGSA - Andaresta, Adhadilah Galuh; Firdaus, Masagus (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This qualitative case study focuses into the use of Quizizz, a digital quiz platform, for integrated language skill assessment in English as a Foreign Language (EFL) classrooms. The study, which was conducted with secondary school instructors and students in Indonesia, looked at how educators use Quizizz to develop exams that include listening, reading, writing, and speaking skills, as well as teacher and student evaluations of its usefulness. Data were collected through semi-structured interviews, classroom observations, focus groups, and assessment material analysis. Thematic analysis found that Quizizz effectively supports the integration of receptive and productive abilities and increases student engagement through gamification, but it presents issues in assessing speaking skills and requires significant instructor work for task design. The findings show the platform's potential for dynamic, motivating language evaluations, while also emphasizing the importance of complementing tools and professional development to address its shortcomings. This study informs the use of digital technologies in comprehensive language skill assessment within EFL situations.